"Ahora que Dios nos ha dado padre […]" El segundo imperio y la cultura jurídico-política campesina en el centro de México - Marino, Daniela (El Colegio de México, A.C., 2006)
The general objective of this text is to explore the conceptions of justice constructed by campesino cultures in central Mexico, both through their own experiences and traditions as well as through their assimilation into liberal culture. It shows how these conceptions illustrate political ideas and practices, such as the appeal to authorities outside the community and the legal path for obtaining recognition of what they considered to be their natural rights – for example, maintaining or recovering access to natural resources or the political administration of their territory. The appeal to justice (whether in the traditional sense, as in the just government that is expected of the authorities, or in the modern sense, strictly following the decisions of judicial authorities) was one of the primary strategies in the collective action repertoire of campesinos.